89.0k views
23 votes
Solve each equation by completing the square.
n^2 – 2n – 48 = -2​

User Lee Benson
by
4.8k points

1 Answer

6 votes

Answer:

n=1+√47 or n=1−√47

Explanation:

Let's solve your equation step-by-step.

n2−2n−48=−2

Step 1: Subtract -2 from both sides.

n2−2n−48−(−2)=−2−(−2)

n2−2n−46=0

For this equation: a=1, b=-2, c=-46

1n2+−2n+−46=0

Step 2: Use quadratic formula with a=1, b=-2, c=-46.

n=

−b±√b2−4ac

2a

n=

−(−2)±√(−2)2−4(1)(−46)

2(1)

n=

2±√188

2

n=1+√47 or n=1−√47

-Bacon

User Stefano D
by
4.5k points